2018
DOI: 10.1186/s12881-018-0625-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel non sense mutation in WDR62 causes autosomal recessive primary microcephaly: a case report

Abstract: BackgroundAutosomal recessive primary microcephaly (MCPH) is a rare genetically heterogeneous disorder of neurogenic brain development characterized by a reduced head circumference at birth with no remarkable anomalies of brain architecture and variable degrees of intellectual impairment. Clinical and genetic heterogeneity in genetic disorders represent a major diagnostic challenge.Case presentationTwo patients, 11 and 9 years old, born from consanguineous parents, were referred to the department of medical ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Most of the reported cases come from countries that allow marriage between relatives. Complex heterozygotes were found only in 11 cases and their clinical picture did not differ significantly from those in which homozygotes were found [ 6 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 94%
“…Most of the reported cases come from countries that allow marriage between relatives. Complex heterozygotes were found only in 11 cases and their clinical picture did not differ significantly from those in which homozygotes were found [ 6 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 94%
“…The WDR62 gene contains 32 exons and is located in the MCPH2 candidate region on chromosome 19q13.12. It encodes a 1523-amino acid protein with multiple WD40 repeats, which are ~ 40-amino acid-long structural motifs that normally end in a tryptophan-aspartic acid dipeptide (Cherkaoui Jaouad et al 2018). A WDR62 null was identified as the second most common cause of MCPH due to the discovery of homozygous missense and frame-shifting mutations in seven MCPH Arab, Pakistani and Caucasian families (Adeline K. Nicholas et al 2010).…”
Section: Wd Repeat Domain 62 (Wdr62/mcph2)mentioning
confidence: 99%
“…Previous studies have identified numerous (>35) patient mutations in WDR62 that are causative of primary microcephaly ( Shohayeb et al, 2017 ; Cherkaoui Jaouad et al, 2018 ; Yi et al, 2019 ). These mutations variously disrupt mRNA stability, splicing or result in the severe truncation WDR62 to trigger nonsense-mediated decay, and lost expression ( Xu et al, 2014 ; Shohayeb et al, 2017 , 2019 ) highlighting that WDR62 expression is required for normal brain growth.…”
Section: Introductionmentioning
confidence: 99%